Lemmus sibiricus Kerr 1792 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
32. Siberian Brown Lemming Lemmus sibiricus French: Lemming de Sibérie / German: Sibirischer Lemming / Spanish: Lemming de Siberia Other common names: Black-footed Lemming, Brown Lemming, Ob Lemming, Siberian Lemming Taxonomy. Mus lemmus sibiricus Kerr, 1792, between Polar Ural Mountains and lower course of Ob River, Yamalo-Nenetskaya Nats. Okr., Russia. Lemmus sibiricus is closely related to L. lemmus and L. amurensis, and in captivity, they hybridize freely. Nevertheless, L. sibiricus consists of several deeply divergent evolutionary lineages. Genetic distances between the most divergent lineages (particularly between west-Siberian and eastSiberian) exceed divergence between west-Siberian lineage of sibiricus and L. lemmus. The idea that all these species are actually conspecific has a long history. The form portenkoi was classified as a separate species until very recently. Molecular assessments placed portenkoi and novosibiricus in the east-Siberian lineage, close to subspecies bungei. Lemmus sibiricus ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 293-294, DOI: 10.5281/zenodo.6707142 ...